Investigative Studies Of Embedded Assembly Line Automation System With Dual Rfid Platform - Abdullah, Samihah (2018)
The lack of control and outdated inventory system have increased the management complexity of factory production lines, especially by the increase of sales and demand in the industry. An unmanageable system in the assembly line leads to inefficiency problems in tracking the volume of the product. The objective of this research is to develop a new design of embedded dual RFID architecture (passive and active systems) into a single system to track and monitor the product delivery process at the assembly lines in the industries. A new combination of 2.4 GHz ZigBee-based RFID operating in wireless sensor network platform is proposed as the solution to the product management problem. Meanwhile, the proposed system involved hardware and software designs which were embedded with the passive RFID reader at Ultra High Frequency (UHF). Results from the experiments conducted showed that the embedded system namely Passive and Active RFID (PAR) produced better overall performance compared to the standalone which Passive RFID (PR) system. The indoor range test was measured from 0 up to 60 m distance. The measurements obtained at 1 m and 60 m of transmission range are -33 dB and -51 dB respectively. It was also observed that embedded system has better signal strength value 7.84 % compared to the standalone system at 60 m. For the highest power level, which is level 4 (10 dBm) it is found that only 0.02 dB of signal loss occurred and matches 99.8 % to the theoretical value for PAR system. The throughput values for the embedded are between 12 kbps to 29 kbps for 17 bytes of data per packet. In the latency test, the embedded PAR system has better and therefore lower delay of 10.9 %, 40.6 % and 74.7 % for up to 3 tags compared to the standalone system. Experimental studies using Design of Experiment (DOE) were also developed using factorial and statistical data analysis to validate the eligibility of the proposed system to be applied in industrial environment and requirements. The factorial analysis on the effects on the conveyor speed, product orientation, tag orientation, type of tags, linear distance and type of product materials had been studied in DOE experiments for guidelines to the industry. The percentage of successful product detection indicates a very high prediction at 97.8 %. The proposed path loss model also provides the estimation of wireless distance and number of assembly lines required for establishing an efficient product management system. From the path loss model at distance 10 m the RSSI value for the NLOS indoor environment of assembly line gave -72 dBm.